Economic Growth and Environmental Sustainability: Empirical Investigation of Bangladesh, India, and Pakistan - Ajibu Jonas; Imran Ali (Universitas Islam Internasional Indonesia, 2026)
This paper examines the long- and short-term relationships between economic growth, trade, industrialization, renewable energy consumption, and environmental degradation in Bangladesh, India, and Pakistan from 1990 to 2022. It uses a panel autoregressive distributed lag (ARDL) approach and employs correlation analysis, panel cointegration tests, and pooled ARDL to capture the dynamic interactions among variables. The results indicate a positive long-term relationship between gross domestic product growth and carbon dioxide emissions, supporting the Environmental Kuznets Curve hypothesis. Trade and industrial growth also have a significant positive impact on emissions in the long run. Conversely, renewable energy consumption consistently shows a negative relationship with carbon dioxide emissions in both the short and long term, highlighting its importance in reducing environmental degradation. The agriculture sector displays a mixed impact, contributing to emissions primarily through land-use changes. The error correction term from the panel ARDL model is statistically significant, confirming long-run equilibrium relationships. The study finds robust evidence of cointegration among the variables, suggesting that the countries are on a convergent path in terms of balancing economic growth and environmental sustainability. Policy recommendations include the enforcement of stricter environmental regulations, promotion of renewable energy, and sustainable trade practices to mitigate environmental harm while fostering economic growth.